Spatial Inequality - Rey, Sergio (REGION, 2025)
This paper explores the concepts and computational methods used to measure spatial inequality, emphasizing a reproducible approach that social scientists can apply to their research. The analysis focuses on geographic income disparities at the sub-national level, using Mexico as a case study. By examining various a-spatial and spatially explicit approaches, the paper highlights the complexities of measuring inequality across places and over time. The discussion includes a review of traditional inequality measures and introduces spatial decomposition methods that account for the geographical distribution of income. The findings underscore the importance of integrating spatial considerations into inequality analysis to better understand the patterns and drivers of regional disparities, thereby informing more effective and equitable policy interventions.